Fatty Liver Is an Independent Risk Factor for Delayed Recovery from Anesthesia. Issue 11 (15th July 2021) - Shapses, Mark; Tang, Lin; Layne, Austin; Beri, Andrea; Rotman, Yaron
Abstract : Fatty liver (FL) is associated with altered activity of hepatic drug‐metabolizing enzymes, but the clinical significance is unknown. Many anesthetic agents are metabolized in the liver. We aimed to determine whether FL impacts recovery from anesthesia as a surrogate for altered drug metabolism. This was a single‐center, retrospective, case‐control study of all adults who underwent anesthesia and concurrent abdominal imaging (n = 2, 021) in a hospital setting. FL (n = 234) was identified through radiology reports. Anesthesia recovery, the primary endpoint, was defined by Aldrete's recovery score (RS, 0‐10), assessed following postanesthesia care unit (PACU) arrival, with RS ≥8 considered discharge eligible. FL and controls were compared using univariate and multivariate analyses, adjusting for confounders. A secondary matched‐pairs analysis matched FL and controls 1:1 for confounders. Time from airway removal to discharge eligibility was compared using multivariate Cox regression. On PACU arrival, 54.1% of FL were discharge eligible compared to 61.7% of controls ( P = 0.03), with lower activity scores on univariate ( P = 0.03) and multivariate analysis ( P = 0.03). On matched‐pairs analysis, discharge eligibility, activity, consciousness, and total RSs were lower in FL ( P ≤ 0.04 for all). Median time from airway removal to discharge eligibility was 43% longer in FL (univariate, P = 0.01; multivariate hazard ratio, 1.32; P = 0.046). To further exclude confounding by obesity, we performed a sensitivity analysis limited to a body mass index <30, where FL was still associated with lower activity ( P = 0.03) and total RS ( P = 0.03). Conclusion: Patients with FL have delayed recovery from anesthesia, suggesting altered drug metabolism independent of metabolic risk factors. Abstract : In this retrospective study, recovery after procedures requiring anesthesia was compared between subjects with fatty liver and those without. Fatty liver was associated with significantly delayed recovery from anesthesia, independent of confounders, suggesting hepatic drug metabolism of anesthetic medications may be altered in these subjects.